Thiol‐Functionalized Palladium Nanoparticles Networks: Synthesis, Characterization, and Room Temperature (Toxic) Vapor Detection. (20th January 2023) - Cerra, Sara; Salamone, Tommaso A.; Bearzotti, Andrea; Hajareh Haghighi, Farid; Mercurio, Martina; Marsotto, Martina; Battocchio, Chiara; Fioravanti, Raoul; Diociaiuti, Marco; Fratoddi, Ilaria
Abstract: The preparation of three different functionalized palladium nanoparticles (PdNPs) systems for room temperature BTX (benzene, toluene, p‐xylene) sensing detection and their morphostructural characterization is described. PdNPs are prepared through a two‐phase water/toluene wet chemical reduction method in the presence of bifunctional organic thiols as stabilizing agents suitable for the formation of covalently linked PdNPs networks: p ‐terphenyl‐4, 4″‐dithiol (PdNPs‐TR), biphenyl‐4, 4′‐dithiol (PdNPs‐BP), or with 9, 9‐didodecyl‐2, 7‐bis(acetylthio)fluorene (PdNPs‐FL). Comparing the hydrodynamic diameter values, TR and BP ligands help to obtain networks consisting of spherical NPs of about 2 nm, in which each bifunctional ligand act as a bridge between PdNPs. In contrast, PdNPs‐FL show a population centered at <2RH > = 45 ± 5 nm. To perform preliminary gas sensing measurements, PdNPs networks are cast deposited on interdigitated electrodes to study their resistive response toward volatile organic compounds (VOCs) such as benzene (0–5%), toluene (0–1.7%), and p ‐xylene (0–0.4%) (BTX) and common interfering gases (H2 S, NH3, SO2, and relative humidity, RH). PdNPs‐FL show enhanced response to BTX with an appreciable response also toward H2 S and RH. PdNPs‐TR exhibit a better ability to discriminate benzene gas with a negligible response after H2 S exposure. Moreover, all the PdNPs systems show little to no response to NH3 and SO2 gases, offering an interesting perspective in practical sensing applications. Abstract : A Hydrophobic interconnected network of PdNPs functionalized with three different bifunctional organic thiols are synthesized via a two‐phase wet chemical reduction method and extensively characterized structurally and morphologically. Sensing performances of PdNPs at room temperature are evaluated following the exposition to different gases: BTX (benzene, toluene, p ‐xylene), H2 S, NH3, SO2, and R.H. to assess response time, selectivity, and sensitivity parameters.